The effectiveness of project-based learning (PjBL) in improving the pancasila student profile (P3) of fourth grade elementary school students in Indonesia - Zaka Hadikusuma Ramadan; Miranti Eka Putri; Muhamad Nukman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model in improving the Pancasila Student Profile (P3) of fourth-grade elementary school students. The study used a quasi-experimental design, comparing the experimental group that implemented PjBL with the control group that used conventional learning. The results showed that students in the experimental group experienced a significant increase in their Pancasila Student Profile scores compared to those in the control group. These findings indicate that the PjBL model is more effective in developing the Pancasila Student Profile, particularly in supporting learning that is oriented towards character building and 21st-century competencies. Therefore, PjBL has the potential to become a strategic learning approach for elementary school learning practices and the implementation of the Merdeka Curriculum.